Mapping Pattern of Locomotor Basic Movement Research - Prasetyo, Tommy Rizki; Sugiana, Sugiana; Muhlisin, Muhlisin; Pasaribu, Ahmad Muchlisin Natas; Rahmawati, Alviani Dyah; Maulana, Amir; Afrinaldi, Rolly; Saputro, Riki Edo; Kardiyono, Kardiyono (Journal Coaching Education Sports, 2025)
This study aims to map the development of research on fundamental locomotor skills within physical education learning over the past decade and to identify existing research gaps. A systematic review method was employed, supported by Publish or Perish software and bibliometric analysis using VOSviewer. Articles were searched from 2012 to 2022 using the keyword “learn basic locomotor movements,” resulting in 2,136 records. The selection and screening process followed the PRISMA protocol, yielding 41 eligible articles. The findings indicate that learning models are the most dominant topic within FMS research, whereas comprehensive investigations of locomotor skills remain limited. Of the 41 articles reviewed, only 18 (43.90%) addressed six locomotor skills, one article (2.44%) covered eight aspects, and none examined all nine locomotor skills (running, jumping, walking, leaping, galloping, sliding, rolling, skipping, hopping). These results highlight a substantial need to develop complete locomotor skill–based learning, particularly for children aged 5–7 years who are in a critical stage of motor development. This study provides an evidence-based foundation for creating more targeted motor intervention programs to support children’s movement competence.